Investigating Past and Present Carpometacarpus Morphology in Mimidae: A Multi-Methods Approach to Evidence from the Guadeloupe Islands. (22nd December 2021) - Jeantet, Nicolas; Ledevin, Ronan; Gala, Monica; Lenoble, Arnaud; Santos, Frédéric; Laroulandie, Véronique
Past bird communities are still under-studied in several Caribbean regions, including the Lesser Antilles. In order to improve our understanding of this area's avifauna, we explore morphometrical variations of the carpometacarpus (CMC) within West Indies Mimidae species. We combine geometric morphometric (GMM) and conventional osteology focusing on characters of the entire or distal portion of the CMC. Morphological variation related to their phylogenetic history is investigated using uni- and multi-variate statistics, and the expression of certain osteological characters. Fossil bone remains from the Guadeloupe Islands were included in the datasets to test the applicability of these results to the archaeological and paleontological record. Our results are consistent with the known phylogeny of Mimidae. The GMM analysis clearly differentiated taxa at both inter- and intra-generic levels, which when combined with osteological characters, allow fossil specimens to be determined to species. For the fossil record of Guadeloupe Islands, this concerns three taxa: the Scaly-breasted Thrasher Allenia fusca, the Gray Catbird Dumetella carolinensis, the first fossil occurrence of this bird in the Greater and Lesser Antilles, and the Brown Trembler Cinclocerthia ruficauda in Desirade and Marie-Galante, where the bird is now extirpated. These results are of particular interest for tracking the impact of environmental changes on the composition of West Indian bird communities.